Acoustic Characterization of a Room: Study Case Between Simulation and a Portable Method - IBARRA-ZARATE, David; PADILLA-ORTIZ, Ana Laura (Archives of Acoustics, 2020)
Large venues and auditoriums are commonly associated with their astounding architecture. Their acoustic quality is an essential factor in its qualification as a great and functional, or a badly designed place. However, acoustics is often overlooked during the design stage of a building due to the complexity and high cost of the measurements involved. For this reason, it is important to explore more accessible ways to implement acoustics evaluations. The aim of this work is to compare typical experimental measuring methods and the use of mobile devices to assess the acoustic quality of a room. These measurements are contrasted with the software simulation of the same acoustical space. The results show that the mobile system can be used for professional measurements with low restrictions in the frequency range of interest of this study (90 Hz to 4000 Hz).